Literary translation and communication - Sun, Yifeng (Frontiers in Communication, 2022)
The translator's main role is that of a communicator—and a cross-cultural one at that. Literary translation communicates more than semantic meaning. A range of literary features is also expected to be reproduced. Reconstructing the literary value and aesthetic experience of the source text is significantly hampered by literary untranslatability. The fundamental purpose of translation is communication, but because it is subject to a multitude of constraints that seriously limit communicative possibilities, literary untranslatability constantly threatens to hinder successful communication. Since translation is often said to transfer the original message to the target reader, communication breaks down when this attempt fails – which occurs more often than not. Literary translation purports to capture, convey and communicate multi-layered and interconnected information and feelings about another situation and community. Any monolithic perception of this inherent irreducibility of all-round functionality is at odds with the nature of literary translation. From a communicative perspective, literary translation aims at developing sophisticated forms to better convey and communicate ideas and feelings, as well as to provide situational cues to elicit appropriate responses from the target reader in tandem with that of the source reader. In light of this, cross-cultural adjustment predicted by contextual conditioning is constantly required to competently communicate the transcultural dimension that is intrinsic to literary translation. Translation is often referred to as a means of cross-cultural or intercultural communication, but how exactly translational communication operates still warrants further investigation. This article aims to examine this relationship from several interrelated aspects and, in this respect, to make a distinction between communication and convey, the latter being a commonly used verb in translation studies.